Beyond Monitoring Functionality to Results Evaluation of eHealth interventions: Development and Validation of an eHealth evaluation framework - Ashaba, Justus; Nabukenya, Josephine (Health Informatics Journal, 2022)
Evidencing eHealth interventions, benefits generates data as a basis for assessing whether observed changes in behavior, processes or healthcare outcomes can be attributed to the eHealth interventions. Generating such evidence requires the use of frameworks or some other type of organizing schemes to help in guiding the process and making sense of eHealth systems and the findings. The frameworks available in literature do not clearly guide on how to monitor eHealth implementation and evaluate eHealth implementation results. This study aimed to develop and validate an eHealth evaluation framework to guide the process of monitoring eHealth implementations and evaluation of eHealth results in terms of outcomes and impact on healthcare in developing countries. The Design Science Research Methodology was followed to conduct this study. Recommendations from an eHealth evaluation exploratory study in Uganda and other eHealth evaluation literature formed key inputs into the design and development of the framework. The framework consists of a generic reference model with eHealth monitoring and evaluation dimensions, performance indicators, and guidelines on how to conduct eHealth monitoring and evaluation. The eHealth evaluation framework received high acceptance (>80%) as regards its fitness for purpose during its validation.
Keywords: results-based management; eHealth; evaluation; monitoring